Hipertensión arterial post-COVID 19 en mujeres de edad avanzada: una secuela de alto riesgo - Bustos-Viviescas, Brian J.; García Yerena, Carlos E.; Villamizar Navarro, Amalia; Lizcano Sánchez, Andrea P.; García Galviz, John A. (CorSalud, 2024)
Hipertensión arterial post-COVID 19 en mujeres de edad avanzada: una secuela de alto riesgo